(untitled) (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Supracondylar fracture of humerus is very common fracture in pediatric age group. The current trends of management in displaced type are close reduction and per cutaneous pinning (CRPP), if reduction is not satisfactory then open reduction and internal fixation (ORIF) is done. Our study aims to compare the cosmetic, functional and radiological outcome between these two methods. Methodology: Children with displaced extension type supracondylar fracture of distal humerus presenting to emergency room and orthopedics OPD who could meet the inclusion criteria were taken up for study. Sixty-three such patients (37 CRPP and 26 ORIF) were included in the study. Radiological and functional outcomes were followed up at 8 weeks post-operatively. Results: Of the 63 patients enrolled, 26 (41.3%) patients had undergone open reduction and internal fixation and 37 (58/7%) had undergone close reduction and percutaneous pinning. The mean age of patients in CRPP and ORIF groups was 7.29±2.3 years and 8.11±2.02 years respectively. Maximum patients were from age group 7-9 years (46%). Left side was more commonly injured (66.7% vs. 33.3%) (P = 0.045). According to the Flynn’s criteria, cosmetically the outcome did not differ between the two surgical groups (P = 0.23). However, CRPP proved to have a significantly better functional outcome (P=0.000). The mean Bauman’s angle in CRPP and ORIF groups was 16.89±5.66 and 18.88±4.90 degrees respectively. However, there is no statistically significant difference between the type of fixation and Bauman’s angle or Anterior humeral line. Conclusions: Close reduction and percutaneous pinning (CRPP) has better functional and radiological outcome in comparison with open reduction and internal fixation (ORIF) in displaced supracondylar fracture of humerus in children.